Making Wall Art Products and Using e-Commerce as Marketing Media - Khairani Puspita; Irwansyah Irwansyah; Daifiria Daifiria (JUDIMAS, 2020)
Technology today plays an important role in all aspects, both in education and in business, such as sales. Currently in business, the role of technology is needed, especially in product sales. E-commerce is a way of doing business that makes it very easy for sellers to market their products. SMA Swasta Budi Agung Medan is one of the schools that is required to produce graduates who can compete and be entrepreneurial. By carrying out this community service, it is aimed at providing insight and knowledge in utilizing technology as an opportunity in entrepreneurship by utilizing e-commerce platforms such as shopee. In addition, students will also be given knowledge about how to make a product using used materials or materials that are available around us. In this training, the products made are wall art products or wall hangings. These products will later be sold or marketed through the e-commerce platform, namely shopee. So, with the implementation of this service, students are expected to be able to be creative and entrepreneurial by utilizing technology properly and correctly.